2009
DOI: 10.1016/j.bbadis.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 subclasses in acute respiratory distress syndrome

Abstract: Phospholipases A2 (PLA2) catalyse the cleavage of fatty acids esterified at the sn-2 position of glycerophospholipids. In acute lung injury-acute respiratory distress syndrome (ALI-ARDS) several distinct isoenzymes appear in lung cells and fluid. Some are capable to trigger molecular events leading to enhanced inflammation and lung damage and others have a role in lung surfactant recycling preserving lung function: Secreted forms (groups sPLA2-IIA, -V, -X) can directly hydrolyze surfactant phospholipids. Cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 197 publications
(132 reference statements)
4
83
0
1
Order By: Relevance
“…Our lung explant studies showed normal rates of choline incorporation into total lipid, but we did not investigate trafficking of lamellar bodies and extracellular release of surfactant material. With regard to degradation, we found no observable increase in PLA 2 , which actively degrades phospholipids and is known to be increased in lavage fluid of children with RDS (66). Albumin, however, was consistently increased in LCAD Ϫ/Ϫ lavage fluid, and albumin has been shown to inactivate surfactant and to possess a phospholipase-like activity (67,68).…”
Section: Discussionmentioning
confidence: 43%
“…Our lung explant studies showed normal rates of choline incorporation into total lipid, but we did not investigate trafficking of lamellar bodies and extracellular release of surfactant material. With regard to degradation, we found no observable increase in PLA 2 , which actively degrades phospholipids and is known to be increased in lavage fluid of children with RDS (66). Albumin, however, was consistently increased in LCAD Ϫ/Ϫ lavage fluid, and albumin has been shown to inactivate surfactant and to possess a phospholipase-like activity (67,68).…”
Section: Discussionmentioning
confidence: 43%
“…Activation of cytosolic phospholipase A 2 in IR mobilizes arachidonic acid for degradation by two main enzymes, lipoxygenase and cyclooxygenase, into several mediators (see below), and these initiate the production of PAF (48). Alveolar macrophages (2) are believed to play a major role in surfactant degradation through excreting lysosomal phospholipase A 2 (108) and are suggested to be responsible for decreased lung compliance after alveolar macrophage depletion with clodronate in a mouse model (212). Type II secreted phospholipase A 2 is another phospholipase A 2 , present in alveolar macrophages, but also in platelets and other cells (108).…”
Section: H1288 Molecular Mechanisms Of Lung Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Alveolar macrophages (2) are believed to play a major role in surfactant degradation through excreting lysosomal phospholipase A 2 (108) and are suggested to be responsible for decreased lung compliance after alveolar macrophage depletion with clodronate in a mouse model (212). Type II secreted phospholipase A 2 is another phospholipase A 2 , present in alveolar macrophages, but also in platelets and other cells (108). A relation has been found between the activation of this type II secreted phospholipase A 2 and subsequent degradation of surfactant (14).…”
Section: H1288 Molecular Mechanisms Of Lung Ischemia-reperfusion Injurymentioning
confidence: 99%
“…The sPLA2 group IIA was initially detected in synovial fluid of patients with rheumatoid arthritis 15,16 . Several studies demonstrated that the sPLA2 group IIA was involved in inflammatory process [17][18][19] and many phospholipases A2 inhibitors have been discovered and their effectiveness have been proved as a treatment of inflammatory diseases [20][21][22] . Because overproduction of these inflammatory mediators might cause inflammatory damage, we focused in the present study on the evaluation of the anti-inflammatory effect of LEJ extracts by measuring the inhibition of the pro-inflammatory sPLA2 group IIA as well as their antioxidant activity.…”
mentioning
confidence: 99%